Facilitating inquiry-based science learning online in a virtual university - Rosalind Kam; Bernard Hoop (Laureate Education Inc, 2013)
The purpose of this paper is to illustrate the authors' interaction-engagement approach in facilitating online courses, which focused on a guided inquiry approach to build understanding of core science concepts using hands-on experimental science investigations. The graduate-level courses were taught during 2005 through 2010, entirely online. The course participants were practicing teachers who were enrolled in the K-8 Science Specialization of a Master of Science in Education degree program. It was presumed that teachers undertook this graduate program to improve their content knowledge, as well as for their professional advancement in their teaching careers and, for some, financial incentives from their state. The courses in this graduate program integrated science and pedagogy; the science and pedagogy components of the courses were facilitated by two different people online: a scientist and a science educator. Most of the program participants were employed fulltime as teachers. For this reason, the weekly sessions began on Fridays to enable them to start their hands-on investigations during the weekend. The authors observed that group discussions and facilitators' postings that foster interactive engagement support collaborative learning among participants in online discussion boards. DOI: 10.18870/hlrc.v3i2.100